2019
DOI: 10.1108/jerer-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Investigating retail property market dynamics through spatial accessibility measures

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.) | P a g eInvestigating Retail Property Market Dynamics through Spatial Accessibility Measures Abstract Purpose: The retail property market is constantly adapting to the continuous demand of retailers and their consumers. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Thus, our study corroborates empirically the existence of significant differences in the brand valuations reported by the three most internationally recognised consultancy companies. This derives from not only the intangible characteristic of brands, but also from there being no active market for selling brands that would allow us to compare market values to the values assigned by the consultants to brands, which occurs with other assets like real estate, for which many studies can be found and have developed sophisticated models (Abidoye et al, 2019;Adebayo et al, 2019;Guadalajara & López, 2018;Lisi, 2019). It is desirable to conduct quantitative works on brand value that contribute to improve our knowledge of the most appropriate methodologies for these assets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study corroborates empirically the existence of significant differences in the brand valuations reported by the three most internationally recognised consultancy companies. This derives from not only the intangible characteristic of brands, but also from there being no active market for selling brands that would allow us to compare market values to the values assigned by the consultants to brands, which occurs with other assets like real estate, for which many studies can be found and have developed sophisticated models (Abidoye et al, 2019;Adebayo et al, 2019;Guadalajara & López, 2018;Lisi, 2019). It is desirable to conduct quantitative works on brand value that contribute to improve our knowledge of the most appropriate methodologies for these assets.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensive and openly accessible data varied by country. For England and Wales, the VOA non-domestic ratings registry has been used by previous studies to for identifying retail locations 11 13 . These data served as the primary source of retail location data; whereas in Scotland and Northern Ireland where VOA data are not available, these were replaced with OSM retail-specific point data 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
“…In the real estate valuations sector, the role of mass appraisal techniques has become strategic: (i) to define the urban policies aimed at the enhancement of exiting property assets [30]; (ii) to develop technical and economic refunctionalization initiatives [31]; (iii) to evaluate the risk related to the provision of mortgage loans by the credit institutions [32]; and iv) to assess the urban planning choices carried out by Public Administration for territorial strategic programs definition [33,34]. According to the International Association of Assessing Officers [35], mass appraisal concerns 'the process of valuing a group of properties as of a given date and using common data, standardized methods, and statistical testing'.…”
Section: Background On Mass Appraisal Techniquesmentioning
confidence: 99%